Smart Working and villages regeneration: towards new resilient practices at the time of Covid-19 - Claudio Pignalberi (Firenze University Press, 2021)
The paper addresses the issue of agile work (smart working) and sustainable development as an innovative response to the (social, cultural, labor) restrictions imposed by Covid-19. With the Serrone Farm Hospitality project we intended to promote a model of social sustainability in a small village in Lazio to understand how the use of agile working practices and the active participation of the subject to informal and non-formal activities can allow the creation of regenerative poles in small villages, that is a container of social and working practices activities, sharing of skills and common participation to the economic, cultural and social design for the revitalization of the territory.   Smart Working e rigenerazione dei borghi: verso nuove pratiche resilienti ai tempi del Covid-19.   Il contributo affronta il tema del lavoro agile (smart working) e dello sviluppo sostenibile come risposta innovativa alle restrizioni (sociali, culturali, lavorative) imposte dal Covid-19. Con il progetto Serrone Farm Hospitality si è inteso infatti promuovere un modello di social sustainability in un piccolo borgo del Lazio per comprendere quanto il ricorso alle pratiche di lavoro agile e la partecipazione attiva del soggetto alle attività informali e non formali possano consentire la creazione di poli rigenerativi nei piccoli borghi, ovvero un contenitore di attività di pratiche sociali e lavorative, di condivisione delle skills e di partecipazione comune al disegno economico, culturale e sociale per il rilancio del territorio.